1996
DOI: 10.1093/molehr/2.9.709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the flow cytometer stain Hoechst 33342 on human spermatozoa

Abstract: Several procedures exist for processing sperm cells for sex preselection. Flow cytometric separation using the fluorochrome stain Hoechst 33342, chemically known as bisbenzimide, is the most promising. The objective of this study was to determine the effect of bisbenzimide on spermatozoa assessed by means of the sperm survival test and to analyse the beta-globin gene in sperm DNA after exposure to increasing concentrations of bisbenzimide. Donor (n = 16) sperm specimens were pooled and washed in a discontinuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…A previous study aimed at the evaluation of mutagenic effects of Hoechst 33342 conducted on human spermatozoa (Watkins et al 1996) revealed possible risks for mutagenesis at high concentrations of dye (O900 mM) after 24 h of exposition. In our study, the high concentrations of dye were used for no more than 15 min, after which sperms were diluted to a concentration that, in the same work, has been demonstrated to be non-mutagenic even after 24-h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study aimed at the evaluation of mutagenic effects of Hoechst 33342 conducted on human spermatozoa (Watkins et al 1996) revealed possible risks for mutagenesis at high concentrations of dye (O900 mM) after 24 h of exposition. In our study, the high concentrations of dye were used for no more than 15 min, after which sperms were diluted to a concentration that, in the same work, has been demonstrated to be non-mutagenic even after 24-h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Nessa técnica de sexagem, o espermatozoide é submetido a vários procedimentos que podem causar danos à célula, tais como exposição ao corante e ao laser, grande pressão na passagem pelo citômetro, queda em grande velocidade dentro do tubo de colheita e permanência durante algumas horas em temperatura ambiente antes de ser processado (Chastant-Maillard & Druat, 2005). Portanto, a queda na motilidade observada no sêmen sexado pode ter sido causada pela exposição, durante o processo de sexagem, ao corante Hoechst 33342, que é tóxico, como já foi demonstrado em espermatozoide humano (Watkins et al, 1996) e bovino (Hollinshead et al, 2004). Além disso, o efeito da exposição ao corante e, posteriormente, ao laser pode alterar a atividade mitocondrial, como foi demonstrado em trabalho realizado por Smith (1993) com ovócitos corados com Hoechst 33342 e submetidos à pequena irradiação de luz ultravioleta.…”
Section: Resultsunclassified
“…The evidence that bisbenzimide Hoechst 33342 at high concentrations (≥900 μ m ) is able to induce point mutations in human sperm was provided using PCR with primers targeting the ß‐globin gene, which was chosen as a representative gene (Watkins et al . ). In the same work, incubating the sperm at a concentration <90 μ m for up to 24 h did not significantly affect the sperm kinetics, nor did this treatment exert any mutagenic effect.…”
Section: Discussionmentioning
confidence: 97%